The determinants of domestic and foreign bond bias - Ferreira, M. A.; Miguel, A. F. (Journal of Multinational Financial Management, 2011)
This paper studies the determinants of the domestic and the foreign bond biases and their evolution over time using aggregate bond allocation data from CPIS. Our results show that the home bias is prevalent across all countries, despite the decreasing of the domestic bias in most countries in the 1997-2009 period. We find that the domestic bond bias is lower in countries with higher economic development, higher restrictions on foreign capital transactions, more developed bond markets, higher familiarity, and higher efficiency of the judicial system. When investing overseas, investors also prefer to allocate their investments in countries with higher economic development, lower restrictions on capital flows, more developed bond markets, stronger judicial systems, and higher past returns. Additionally, we find that familiarity (i.e. geographic proximity, common language, and bilateral trade) is a major determinant to decrease the foreign bias. Finally, there is no evidence that investors' bond allocations are explained by diversification opportunities as proxied by bond markets correlations.